Analysis of Sharia Policy and Remuneration on Professionalism Through Human Resources - Amiur Nuruddin; Saparuddin Siregar; Dahrani Dahrani (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2022)
Islamic banking as a business institution based on sharia values ​​and principles, the qualifications and quality of human resources clearly demands an integration between "Knowledge, skill and ability" with moral commitment and personal integrity. Emphasis on the aspect of morality, which in this trend is believed to be the key success factor for the "key success factor" in business management, financial institutions and Islamic banking, namely Al-siddiq (true, honest), Al-amanah (trusted, credible), Al- tabligh (communicative, transparent) and al-fatanah (smart, professional) are as important as knowledge, abilities and skills. JeThe type of research used in this research is quantitative research with causality research design. Quantitative research method is a research method with data in the form of numbers and analysis using statistics. Based on the philosophy of positivism and is a scientific/scientific method because it has fulfilled scientific principles, namely concrete/empirical, objective, measurable, rational and systematic variablesremuneration policy directly significant effect on professionalism. Sharia Remuneration variable directly has a significant effect on professionalism. Human resources variables directly have a significant effect on professionalism, Sharia remuneration indirectly through human resources has an insignificant effect on professionalism, Sharia remuneration variables directly have no significant effect on human resources, variableremuneration policy directly does not have a significant effect on professionalism.